Paratesticular Mesenchymal Malignancies: A Single-Center Case Series, Clinical Management, and Review of Literature. (January 2020) - Gatto, Lidia; Del Gaudio, Massimo; Ravaioli, Matteo; Cescon, Matteo; Tonini, Valeria; Cervellera, Maurizio; Franceschelli, Alessandro; Pirini, Maria Giulia; Di Scioscio, Valerio; Buia, Francesco; Niro, Fabio; Capizzi, Elisa; et al.
Background: Primary soft tissue sarcomas arising from the male urinary and genital tract are rare tumors, only accounting for 1% to 2% of all malignancies of the genitourinary tract. Clinical management of advanced disease is lacking in standardized recommendations due to the rarity of the disease. To date, complete and extensive surgery represents the only curative and standardized approach for localized disease, while the impact of retroperitoneal lymphadenectomy and adjuvant treatments on clinical outcomes are still unclear. Similarly, a standardized systemic treatment for advanced metastatic disease is still missing.Cases Presentation: Four out of 274 patients have been identified in our sarcoma population. The mean age was 54 years (range = 45-73). The histotypes showed liposarcoma in 2 cases and leiomyosarcoma in the remaining 2 cases. In all 4 cases, the disease was localized at presentation, patients underwent complete surgery, and no adjuvant treatments were done. Three cases presented a recurrence of disease at a mean follow-up of 86 months (range = 60-106 months), more than 7 years. Two cases were treated with a second surgery and chemotherapy and 1 case only with chemotherapy.Discussion and Conclusions: Sharing data about clinical management of paratesticular mesenchymal tumors is a key issue due to the rarity of this tumor's subtype. In this article, we report the clinical history of 4 patients affected by paratesticular mesenchymal tumor. In particular, main issues of interest are the decision of postoperative treatment and systemic treatment at time of disease recurrence.